2017
DOI: 10.1093/mnras/stx1159
|View full text |Cite
|
Sign up to set email alerts
|

The rest-frame Golenetskii correlation via a hierarchical Bayesian analysis

Abstract: Gamma-ray bursts (GRBs) are characterised by a strong correlation between the instantaneous luminosity and the spectral peak energy within a burst. This correlation, which is known as the hardness-intensity correlation or the Golenetskii correlation, not only holds important clues to the physics of GRBs but is thought to have the potential to determine redshifts of bursts. In this paper, I use a hierarchical Bayesian model to study the universality of the rest-frame Golenetskii correlation and in particular I … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The relation between the energy flux F and E p , i.e., the Golenetskill E p -F relation (Golenetskii et al 1983;Burgess 2019), for the time-resolved spectra of GRB 131231A is shown in Figure 4a. Previous analyses (e.g., Borgonovo & Ryde 2001;Firmani et al 2009;Ghirlanda et al 2010;Yu et al 2018) have revealed that the Golenetskill E p -F relation shows three main types of behavior: a non-monotonic relation (containing positive and negative power-law segments, with a distinct break typically at the peak flux), a monotonic relation (described by a single power law), and no clear trend.…”
Section: Parameter Correlation Analysismentioning
confidence: 99%
“…The relation between the energy flux F and E p , i.e., the Golenetskill E p -F relation (Golenetskii et al 1983;Burgess 2019), for the time-resolved spectra of GRB 131231A is shown in Figure 4a. Previous analyses (e.g., Borgonovo & Ryde 2001;Firmani et al 2009;Ghirlanda et al 2010;Yu et al 2018) have revealed that the Golenetskill E p -F relation shows three main types of behavior: a non-monotonic relation (containing positive and negative power-law segments, with a distinct break typically at the peak flux), a monotonic relation (described by a single power law), and no clear trend.…”
Section: Parameter Correlation Analysismentioning
confidence: 99%
“…The power-law slopes for the relationships obtained by Lu et al [179] and Guiriec et al [39] are slightly different from one another, which shows that the rest frame correlation is not well constrained. Burgess [180] used statistical methods to show that the current formulation of the Golenetskii relationship is not well constraining, at least in the context of using the relationship to detemine the redshifts of GRBs. They suggest adding terms to the relationship that can account for other physical parameters of GRBs such as the opening angle to make this relationship more universal among all GRBs.…”
Section: Golenetskii (Hardness-intensity) Relationmentioning
confidence: 99%
“…Theories predicting and explaining the Golenetskii relation are still in development [126,180], but there are a few results that have been obtained under each prompt emission model.…”
Section: Physical Interpretationmentioning
confidence: 99%